Assessment of a Decision-Making Model for Monitoring the Success of a Project for Smart Buildings - Serag Amhaimedi; Sepanta Naimi; Sura Alsallami (Civil Engineering Journal, 2023)
Objective: To express the usage of intelligent concepts in the architectural building construction field that are primarily concerned with reducing building energy use. Improved energy-saving methods and the use of environmentally friendly design principles are essential in this field. This type of managerial decision-making is necessary for the success of these types of projects. Methods: monitoring the performance of intelligent buildings use the cost variance (CV) and schedule variation as standard metrics to track the progress of a project based on the save energy concept. Also, this research conducted a comparative study on Building Information Modelling (BIM) and (MCDM) decision-making limitations as presented in the article. Analysis: the conventional technique, on the other hand, is unable to offer data on variance from typical performance levels. The main point based on Delphi results of construction cost variables has been observed 19 effective factors. Finding and Novelty: The RII observed that the most effective aspects of an intelligent building are the number of floors in the building, the kind of structural design, and the size of the shadow cast on the surface of the building. The Multi-Criteria Decision Maker (MCDM) observed significant differences in planned value (PV) and actual value (AC) results. In addition, as a result of the current approach, it is possible to track project costs and timelines more precisely. Doi: 10.28991/CEJ-2023-09-01-010 Full Text: PDF